ANALISIS PENERAPAN MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN DISIPLIN KERJA PEGAWAI PADA CV. PAWER RENJES MUARA TEWEH KABUPATEN BARITO UTARA - Boby Saputra Boby; Andre Fajar Al Akbar (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2026)
The purpose of this study was to determine and analyze the implementation of human resource management in improving employee work discipline at CV. Pawer Renjes Muara Teweh, North Barito Regency, and to identify the factors influencing employee work discipline. This study used a qualitative approach with research subjects consisting of the leader, administrative staff, and operational employees at CV. Pawer Renjes Muara Teweh, totaling seven informants. Data were collected through interviews, observation, documentation, and literature study. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that the implementation of human resource management at CV. Pawer Renjes Muara Teweh has been carried out through workforce planning, employee recruitment, employee development, compensation, and supervision and discipline guidance. The level of employee work discipline in terms of attendance, punctuality, and compliance with work regulations was categorized as fairly good. Factors influencing employee discipline include workforce planning, employee development, compensation, and supervision. Overall, the implementation of human resource management plays a role in improving employee work discipline in the company.